Analysis of Acceptance And Use of Learning Management System Using The UTAUT Model (Case study: STMIK Logika): Analysis of Acceptance And Use of Learning Management System Using The UTAUT Model (Case study: STMIK Logika) - Mayu Rina Dwita (Institute of Computer Science (IOCS), 2020)
Web technology is the result of a set or organized activities and procedures which are the development of renewable information system technology where the development of the application uses the Android system model. The development of the website system and its application creates an ease in providing information, especially in the material or teaching material at which the Covid-19 outbreak is currently happening. This learning system indirectly provides information to the public and students, especially in the form of knowledge and information related to knowledge in a particular field of science. STMIK Logika applies the learning system as a medium for online learning in addition to face to face directly. Learning system developed with the aim of improving the quality and effectiveness of learning that offers several facilities such as online assignments, online tests, lecture materials and so on. To find out the behavior in the use of e-learning, the UTAUT (Unified Theory of Acceptance and Use of Technology) model is used. The results of the study are in the form of Performance Expansion (PE), Business Expansion (EE), Social Influence (SI) and Facilitating (FC) variables that have a significant effect on User Acceptance Interest (BI). Overall, all of these predictor variables are able to explain the effect on user acceptance interest. the UTAUT (Unified Theory Of Acceptance And Use Of Technology) model is used. The results of the study are in the form of Performance Expansion (PE), Business Expansion (EE), Social Influence (SI) and Facilitating (FC) variables that have a significant effect on User Acceptance Interest (BI). Overall, all of these predictor variables are able to explain the effect on user acceptance interest. the UTAUT (Unified Theory Of Acceptance And Use Of Technology) model is used. The results of the study are in the form of Performance Expansion (PE), Business Expansion (EE), Social Influence (SI) and Facilitating (FC) variables that have a significant effect on User Acceptance Interest (BI). Overall, all of these predictor variables are able to explain the effect on user acceptance interest.